Previsão dos níveis freáticos induzidos pelo Reservatório da Usina Hidrelétrica Bem-Querer, RR - Freitas, Fabrício Nunes de (2024)
The project of the Bem Querer Hydroelectric Power Plant (UHEBQ), in the state of Roraima, indicates that the reservoir will have a flooded area of approximately 519 km². The impacts on the physical, biotic, and social environment could be significant, which have been estimated in previous studies conducted by stakeholders in this venture. However, the impacts on groundwater were not addressed in the inventory studies. In this context, this study presents the results of modeling the potential impacts of the UHEBQ reservoir on the Static Levels (NE) of the aquifers in its surroundings. For this purpose, 2D mappings of the average depth and NE top elevation of the aquifers around the UHEBQ reservoir were conducted, as well as simulations of the spatial variation of hydraulic head in 10 sections along the longitudinal axis of the reservoir. The results indicated a potential flooding of relatively distant areas from the reservoir due to the water table rise caused by an 8% increase in NE due to artificial recharge of the aquifers induced by the reservoir. It was also possible to observe the previously unknown existence of spatial heterogeneities in the aquifer top surface, indicating the presence of different hydrofacies with varying porosity and permeability of the aquifer layers. Due to the significant lack of data regarding Roraima's aquifers, the results presented here indicate the need for further studies for a more accurate assessment of the potential impacts that the UHBQ reservoir may have on the groundwater in its surroundings.